8.3k views
3 votes
Someone please expain how to do this, i’m really confused.

Someone please expain how to do this, i’m really confused.-example-1

2 Answers

3 votes

Answer:g(4)=13

Explanation:

g(4)=25-3r

25-3(4)

25-12

g(4)=13

User INeal
by
5.8k points
3 votes

Answer:

13

Explanation:

Basically, we have to plug in 4 for r into g(r). Doing so gives us g(4) = 25 - 3 * 4 = 25 - 12 = 13.

Some more examples:

g(6) = 25 - 3 * 6 = 25 - 18 = 7

g(1) = 25 - 3 * 1 = 25 - 3 = 22

User Epicurus
by
4.9k points